2021
DOI: 10.1038/s41598-021-97730-5
|View full text |Cite
|
Sign up to set email alerts
|

Duchenne muscular dystrophy cell culture models created by CRISPR/Cas9 gene editing and their application in drug screening 

Abstract: Gene editing methods are an attractive therapeutic option for Duchenne muscular dystrophy, and they have an immediate application in the generation of research models. To generate myoblast cultures that could be useful in in vitro drug screening, we have optimised a CRISPR/Cas9 gene edition protocol. We have successfully used it in wild type immortalised myoblasts to delete exon 52 of the dystrophin gene, modelling a common Duchenne muscular dystrophy mutation; and in patient’s immortalised cultures we have de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…RNA was extracted from muscle cryosections (RNeasy mini kit; QIAGEN, Hilden, Germany). RT was performed using 750ng of total RNA with SuperScript IV Reverse Transcriptase (Invitrogen, Waltham, MA), and nested PCR of cDNA samples was carried out using specific primer pairs (hybridizing in DMD exons 41, 43, 44–58, 59, and 60) as previously described 27 . PCR products were analyzed on 1% agarose gels, and DNA was purified (Gel Extraction Kit; Omega Bio‐Tek, Norcross, GA) and validated via Sanger sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…RNA was extracted from muscle cryosections (RNeasy mini kit; QIAGEN, Hilden, Germany). RT was performed using 750ng of total RNA with SuperScript IV Reverse Transcriptase (Invitrogen, Waltham, MA), and nested PCR of cDNA samples was carried out using specific primer pairs (hybridizing in DMD exons 41, 43, 44–58, 59, and 60) as previously described 27 . PCR products were analyzed on 1% agarose gels, and DNA was purified (Gel Extraction Kit; Omega Bio‐Tek, Norcross, GA) and validated via Sanger sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…(dystriphin-targeted therapies), such as adeno-associated virus (AAV)-mediated micro/minidystrophin gene delivery, synthetic antisense oligonucleotides for exon skipping, nonsense readthrough, CRISPR-Cas9 (clustered regularly interspaced short palindromic repeat-CRISPR-associated protein 9)-mediated genome editing, protein replacement therapies, and primarily utropin; (2) the therapy of downstream pathological changes, such as transplantation of muscular stem cells, corticosteroids (prednisolone or deflazacort) with highly effective in therapy of concomitant destructive processes (namely inflammation) and an improvement in calcium homeostasis, leading to a decrease in oxidative stress in muscle tissue, and in mitochondrial function and biogenesis [45][46][47][48][49][50][51][52][53][54][55] (Figure 1). Currently, gene editing is attracting attention as a therapeutic strategy for DMD because of the restoration of the dystrophin reading frame in more than 40% of all patients with DMD [56][57][58][59][60][61][62][63]. However, it has been reported that clinical trials with this strategy have to be discontinued because of off-target effects that cause chromosomal abnormalities.…”
Section: Therapy Strategy Of Dmdmentioning
confidence: 99%
“…Muscle cell cultures gained directly from DMD patients appear to be the preferred choice, but there is very limited access to these as diagnosis for DMD today does no longer require a muscle biopsy but is based on genetic diagnosis [ 13 ]. Thus, methods like immortalization of human muscle cells [ 14 ], CRISPR/Cas9 gene editing to create DMD models, using immortalized cells [ 15 ], or reprogramming of different cell types (e.g., urine derived cells, [ 16 ]) have been employed [ 17 ]. However, benefits of these model systems should be weighed against possible disadvantages, since cellular senescence is a contributing factor in DMD [ 18 ], a readout that will be lost in immortalized cells.…”
Section: Introductionmentioning
confidence: 99%